Risky sexual practices among men who have sex with men in Northeast Brazil: results from four sequential surveys Práticas sexuais de risco de homens que fazem sexo com homens no Nordeste do Brasil: resultados de quatro inquéritos seqüenciais - Rogério Costa Gondim; Ligia Regina Franco Sansigolo Kerr; Guilherme L. Werneck; Raimunda Hermelinda Maia Macena; Marta Kerr Pontes; Carl Kendall (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
This paper focuses on recent trends in risky sexual practices for HIV/AIDS among men who have sex with men (MSM) in Fortaleza, Ceará State, Brazil. Four cross-sectional surveys were conducted (1995, 1998, 2002, and 2005) among MSM 14 years or older who reported oral or anal sex in the previous 12 months. Sexual practices were considered risky whenever the respondent reported unprotected receptive or insertive anal intercourse in the six months preceding the interview. Different selection techniques were used to recruit the study population: snowball (1995, 1998, 2002 - 32%); time-space sampling (2002 - 68%); and respondent-driven sampling (2005). Analyses were based on the comparison between proportions. High rates of risky sexual practices were reported in 1995 (49.9%), decreasing in 1998 (32.6%), increasing again in 2002 (51.3%), and showing the lowest level in 2005 (31.4%). Participants with more schooling increased their risky practices from 1998 to 2002, decreasing in 2005. Among individuals with medium or low schooling, risky behavior declined from 2002 to 2005. The article highlights the need for behavioral surveillance to properly address STD/HIV prevention. Estudaram-se as tendências recentes das práticas sexuais de risco para DST/AIDS entre homens que fazem sexo com homens (HSH) em Fortaleza, Ceará, Brasil. Realizaram-se quatro estudos seccionais (1995, 1998, 2002 e 2005) em HSH, com 14 anos ou mais, que tenham referido prática sexual oral ou anal com homens nos últimos 12 meses. Definiu-se prática sexual de risco uma relação anal insertiva ou receptiva sem uso de preservativo nos seis meses que antecederam a entrevista. Utilizaram-se técnicas de recrutamento do tipo snow ball (1995, 1998, 2002 - 32%); time space sampling (2002 - 68%) e respondent driven sampling (2005). Análises basearam-se nas comparações entre proporções. Elevados percentuais de práticas sexuais de risco foram referidos em 1995 (49,9%), decrescendo em 1998 (32,6%), crescendo em 2002 (51,3%) e apresentando os menores percentuais em 2005 (31,4%). Indivíduos com escolaridade mais elevada aumentaram as práticas de risco entre 1998 e 2002, decrescendo no último período. Nos de estrato de escolaridade baixa ou média observou-se declínio no comportamento de risco entre 2002 e 2005. Os resultados deste estudo salientam a importância da vigilância comportamental para adequação dos programas de prevenção das DST/AIDS nessa população.